An investigation into optimizing nuclear power plant outage durations - Obaray, Shaheed (Department of Electrical Engineering, 2024)
There is a compelling rationale for outage optimization as it presents numerous benefits for the Nuclear Power Plant (NPP) and accordingly, for the economy of a country, the environment, and society. An outage delay of one day has been reported to be equivalent to a loss of USD1.5m-2m per day, not to mention the economic costs to a country's economy due to load shedding or disruption of the electricity supply. The reduction of average outage durations from 106 days to 38 days in the USA has been shown to negate the need to build 25-30 NPPs during a defined period. The main aims of this research study were to investigate the value of optimization and to explore practices and methods that contribute to successful outage optimization. There was limited published research on the topic and this dissertation aimed to contribute actionable knowledge to improve outage optimization. Optimization practices were investigated by accessing and reviewing a body of literature, followed by interviews with 12 nuclear outage maintenance specialists or experts from the USA and South Africa, with extensive experience to identify perspectives on trends and key information to answer the research questions. The analysis identified key methods or practices that contribute to successful optimization. The factors that led to longer than required outages and outage delays were found to be closely related to the proposed optimization methods. These included, 1) the need to enhance planning, which includes scheduling, risk management and contingencies; 2) the importance of ensuring the right resources with the right skill levels of those executing outages featured high on the agenda; 3) the need for improved work practices as part of a continuous improvement effort and culture. This study found that NPPs can do more to achieve optimized, best duration outages. There were indeed some key, immediately actionable practices and methods that if replicated, favored optimization success. It is evident that NPPs can do significantly better on outage durations, motivating for further investigation and improvement.